Proceedings of the 18th Annual Conference on Information Technology Education 2017
DOI: 10.1145/3125659.3125695
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Academic Success Based on Learning Material Usage

Abstract: In this work, we explore students' usage of online learning material as a predictor of academic success. In the context of an introductory programming course, we recorded the amount of time that each element such as a text paragraph or an image was visible on the students' screen. Then, we applied machine learning methods to study to what extent material usage predicts course outcomes. Our results show that the time spent with each paragraph of the online learning material is a moderate predictor of student su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Although such resources are widely used and studied across disciplines, there is a growing body of work specifically focused on their use in introductory programming. Some researchers have applied techniques for machine learning [323,370] and data mining [36] to study interaction by introductory programming students with an LMS in order to identify behaviour patterns and investigate whether these can predict academic success. Other papers focus on introductory programming students' use of specific types of resource provided within a learning environment, such as video lectures [149,428] and interactive reading and homework materials [183] designed to enable a flipped classroom approach.…”
Section: Student Behaviourmentioning
confidence: 99%
“…Although such resources are widely used and studied across disciplines, there is a growing body of work specifically focused on their use in introductory programming. Some researchers have applied techniques for machine learning [323,370] and data mining [36] to study interaction by introductory programming students with an LMS in order to identify behaviour patterns and investigate whether these can predict academic success. Other papers focus on introductory programming students' use of specific types of resource provided within a learning environment, such as video lectures [149,428] and interactive reading and homework materials [183] designed to enable a flipped classroom approach.…”
Section: Student Behaviourmentioning
confidence: 99%
“…Results show that the students who followed the personalized guidance and recommendations performed better in exams. The usage of online learning material (in an introductory programming course) was used to predict academic success [27]. The results obtained have shown that the time spent with the material is a moderate predictor of student success.…”
Section: Programming Coursesmentioning
confidence: 99%
“…Other studies track interactions with online learning materials offered as a part of the course. Leppänen et al monitored how long each element, be it a paragraph or an image, of the online textbook was visible on each student's screen [11]. Similarly, Yang et al collected clickstream data from students watching lecture videos in a massive online open course (MOOC) and used time series machine learning techniques to develop a predictor to much success [24].…”
Section: Recent Studiesmentioning
confidence: 99%
“…The nature and source of such data vary greatly. Examples include student programming behavior, assignment performance, clicker data, and question-and-answer interactions on online forums [10][11][12]. These recent studies improved our understanding of the characteristics of low-or high-performing students, as well as the extent to which machine learning can predict struggling students.…”
Section: Introductionmentioning
confidence: 99%